Pemanfaatan Lahan Pekarangan dengan Sistem Hidroponik dan Limbah Botol Plastik untuk Mengurangi Pencemaran Lingkungan di Desa Kertasemaya, Kabupaten Indramayu - Yudianto, Agus; Nurpratama, Meddy; Firdaus, Taufansyah; Sonjaya, Nana Supriatna (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service initiative began in response to environmental issues in Kertasemaya Village, where the lack of waste disposal facilities led some residents to improperly dispose of organic and non-organic waste, particularly in irrigation rivers, causing blockages. The increasing volume of plastic bottle waste requires proper management to prevent pollution. The community's awareness of waste management in Kertasemaya Village is still low. Several training sessions were conducted to address this problem, including education on hydroponic practices and the creation of simple planting media using discarded bottles, rock wool, and flannel fabric. Housewives showed interest in the hydroponic system and expressed their willingness to implement it at home. This training aims to enhance community awareness about waste management and the beneficial use of plastic bottles. The program aims to provide knowledge and skills regarding the utilization of yard spaces through hydroponic systems by using plastic bottle waste to minimize environmental pollution in Kertasemaya Village. The success of the training was measured by comparing participants' knowledge before and after the training. Pretest and posttest results showed that 93% of participants experienced an increase in knowledge, while 59% showed no improvement.